Validity and responsiveness of a new measure of knee osteophytes for osteoarthritis studies: data from the osteoarthritis initiative. Issue 12 (December 2015) - Hakky, M.; Jarraya, M.; Ratzlaff, C.; Guermazi, A.; Duryea, J.
Summary: Purpose: To validate a novel quantitative MRI method to measure osteophyte volume. Methods: 90 subjects were selected from the Progression Cohort of the Osteoarthritis Initiative (OAI) at baseline and 48 months, and analyzed using a semi-automated software tool. Marginal osteophyte volume was calculated for four compartments of the central weight-bearing region of the tibiofemoral joint. Standardized response mean (SRM) for change in volume was used to quantify responsiveness. Concurrent validity was assessed via a comparison with MRI Osteoarthritis Knee Score (MOAKS) using Kruskal–Wallis analysis and Spearman's correlation coefficient. Intra- and inter-reader reliability was assessed on a subset of 20 knees using intra-class correlation coefficients (ICCs) and the root mean square standard deviation (RMSSD). Results: The average change in osteophyte volume (ΔV) was 196 mm 3 (SD = 272 mm 3 ), and the baseline to 48-month SRM was 0.72. An increase in osteophyte volume was observed for 84% (76/90) of the subjects. Kruskal–Wallis analysis across the four MOAKS osteophyte categories was significant for medial and lateral compartments of both the tibia and femur ( P  < 0.001 for all). The intra-reader ICC was 0.98, and RMSSD was 82 mm 3, while inter-reader ICC was 0.97 and RMSSD was 91 mm 3 . A statistically significant positive correlation was observed between osteophyte volume and several MOAKS cartilage and BML scores. The reader time was approximately 10 min per knee. Conclusions: The method is responsive, efficient, and precise, making it practical for use in large cohort studies and observational research.